Machine Bank: Own Your Virtual Personal Computer - Tang, Shuo; Chen, Yu; Zhang, Zheng (IEEE Computer Society, 2007)
In this paper, we report the design, implementation and experimental results of Machine Bank, a system engineered towards the popular shared-lab scenario, where users outnumber available PCs and may get different PCs in different sessions. Machine Bank allows users to preserve their entire working environment across sessions. Each client runs virtual machine, which is saved to and reinstantiated from a content-addressable backend storage. We carefully designed lightweight hooks at client side that implements caching and tracking logics to improve reinstantiation speed as well as to remove unnecessary network and disk traffic. Our detailed evaluation demonstrates that these techniques are effective, and the overall performance fits well with the shared-lab usage.